Equine influenza: A current reference for vets in practice in the UK. (1st September 2019) - Rendle, David; Ivens, Philip; Bowen, Mark; Lawrence, Hattie; Newton, Richard; Marr, Celia; Paillot, Romain; Rash, Adam
Abstract : Foreword: This document was commissioned to provide veterinary surgeons with up-to-date information on equine influenza (EI) and the situation that has developed through 2019. The content of the document and practical recommendations were developed using an informal modified two-round Delphi process, considering published and unpublished research relating to EI using a roundtable forum and online discussion. Where research evidence was conflicting or absent, collective expert opinion, based on the experience of the group, was applied. The opinions expressed are the consensus of views expressed by the authors who all approved the final manuscript. Where an agreement was not reached, opposing views are presented such that readers can understand the arguments. The expert group was organised by UK-Vet Equine and the meeting held at Stanstead Airport on 11 July 2019 with sponsorship from MSD. The sponsors did not participate in the meeting and had no input to or sight of the resultant manuscript prior to publication.